Peningkatan Keterampilan Penyusunan Laporan Keuangan Berbasis ETAP dengan Aplikasi SIA BUMDes Tasikmalaya - Edi Fitriana Afriza; Bakti Widyaningrum; Betanika Nila Nirbita; Iis Aisyah (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The fact is that in the field there are still BUMDes that are constrained and lack of understanding in the preparation of financial statements either manually or the use of the application provided. The purpose of the service is to provide education and training on the preparation of BUMDes financial statements according to SAK ETAP to understand the basis for correct accounting records at BUMDES, partners can compile SAK ETAP-based financial statements correctly and can use the SIA BUMDES application in making SAK ETAP-based financial reports. The methods used in this service are providing counseling, education, training (tutorials and exercises) and evaluating activities using questionnaires. Based on the implementation of service activities that have been carried out, the conclusions obtained are: 1) The management of BUMDes Cakrabuana and BUMDes Nanjung have been able to understand the benefits and basis of good and correct accounting records to be able to improve the performance of their respective BUMDes; 2) The management of BUMDes Cakrabuana and BUMDes Nanjung are able to make good SAK ETAP-based financial statements starting from income statements, capital change statements, balance sheets, cash flow statements, and notes to financial statements; 3) The management of BUMDes Cakrabuana and BUMDes Nanjung understands the use of the SIA BUMDes application which will later help BUMDes in monitoring the performance of these BUMDes and will make financial reports on BUMDes more transparent and accountable.